임도 개설에 따른 조류의 행동권 변화에 관한 연구 - 한승우(Seung Woo Han); 진선덕(Seon Deok Jin); 임은홍(Eun Hong Lim); 최성훈(Sung Hoon Choi); 이준우(Joon Woo Lee) (한국조류학회지, 2019)
본 연구는 임도 개설이 조류의 행동권에 미치는 영향을 파악하기 위해 민주지산을 대상으로 수행하였다. 조사지역에서 관찰된 조류는 총 42종 879개체(최대 개체수의 합)이었고, Site 3구간에서 36종 335개체로 가장 많았다. 우점종은 노랑턱멧새, 오목눈이, 붉은머리오목눈이, 박새, 쇠박새, 쑥새의 순으로 상위 5% 이상 우점한 것으로 분석되었다. 임도의 Site별 행동권 변화는 상위 5% 우점종을 대상으로 관찰 지점에 대한 좌표를 활용하여 분석하였다. Site 1의 MCP에 의한 행동권은 7.18ha(Median)이었다. KDE 90%는 4.71ha(Median)이었고, 70%는 0.76ha(Median)이었으며, 핵심서식지인 KDE 50%는 0.12ha(Median)이었다. Site 2의 MCP는 7.90ha(Median)이었고, KDE 90%은 4.92ha(Median), KDE 70%은 0.88ha(Median)이었다. 핵심 서식지인 KDE 50%는 0.06ha(Median)이었다. Site 3의 MCP는 3.74ha(Median)이었다. KDE 90%는 3.38ha(Median)이었고, KDE 70%는 0.45ha(Median), 핵심 서식지인 KDE 50%는 0.12ha(Median)이었다. 임도 개설로 인해 조류의 행동권에 변화가 나타났고, 이는 서식지 단편화 등의 우려가 있어 관리가 필요하다. This study was conducted to investigate the effect of forest road construction on the home-range of birds in Mt. Minjuji-san. The total number of birds observed in the survey area was 879 individuals in 42 species (sum of the maximum number), and the largest number was 36 species and 335 in 3 site. The dominant species was analyzed in the top 5% in order of Emberiza elegans, Aegithalos caudatus, Paradoxornis webbianus, Parus major, Parus glandarius, Emberiza rustica. Changes in home-range by sites in Forest Road were analyzed using the coordinates of observation points for the top 5% dominant species. The home-range by MCP at Site 1 was 7.18 ha (Median). KDE 90% was 4.71ha (Median), 70%, 0.76ha (Median), KDE 50%(core area), 0.12ha (Median), respectively. The MCP of Site 2 was 7.90ha (Median), KDE 90%, 4.92ha (Median), KDE 70%, 0.8ha (Median), respectively. KDE 50%(core area) was 0.06ha (Median). MCP of Site 3 was 3.74 ha (Median). KDE 90% was 3.38ha (Median), KDE 70%, 0.45ha (Median), and KDE 50%(core area), 0.12ha (Median), respectively. KDE 90% was 3.38ha (Median), KDE 70% was 0.45ha (Median) and the core habitat KDE 50% was 0.12ha (Median). Forest road construction has brought about changes in the home-range of birds, which need to be managed because of concerns about fragmentation of habitats. KCI Citation Count: 2